Thermal Conductivity Enhancement of Al2O3 and SiO2 Nanolubricants for Application in Automotive Air Conditioning (AAC) System - Redhwan, A. A. M.; Azmi, W. H.; M. Z., Sharif; Nurul Nadia, Mohd Zawawi (EDP Sciences, 2017)
Nanolubricant been introduced in compressor might improve the performance of automotive air conditioning system. Prior testing of the nanolubricant enhancement performance, thermal conductivity of Al2O3/PAG and SiO2/PAG nanolubricants has to be investigated and compared. Al2O3 and SiO2 nanoparticles first been dispersed in Polyalkylene Glycol (PAG) for different volume concentrations. KD2 Pro was used in determining the thermal conductivity of the nanolubricant. The experimental results showed that the thermal conductivity of the Al2O3/PAG and SiO2/PAG nanolubricants increased by volume concentration but decreased by temperature. The highest thermal conductivity was observed to be 0.153 W.(mK)-1 and enhancement of 1.04 times higher than the base lubricant for Al2O3 with 1.0 volume concentration. Finally regression equations were developed in order to estimate the thermal conductivity for these nanolubricants.